Perancangan Lapis Pondasi Agregat Tanpa Penutup Aspal Pada Gradasi Batas Tengah Dengan Menggunakan Clay Stone - Ahmad Norhadi; H. Muhammad Fauzi; Akhmad Marzuki; Zuraida Zuraida (Jurnal Teknik Sipil, 2018)
â€œLapis Pondasi Agregat tanpa penutup aspalâ€ is a strong layer structure because it receives a direct load of vehicles above the surface. In general, the making of access roads for mining sites does not use pavement with asphalt. One of the materials for mining pavement generally uses the mine's surface excavation using a clay stone as an addition to a mixture or filler for the aggregate layer structure. Clay stone is a sedimentary rock that is strong if it is in the soil and will become soft when submerged in water. â€œLapis Pondasi Agregat tanpa penutup aspalâ€ is dominated by fine particles which is a maximum diameter of 19 mm making it difficult to adjust the gradation composition. So to get the ideal gradation of â€œLapis Pondasi Agregat tanpa penutup aspalâ€ composition, it is necessary to do Research on â€œLapis Pondasi Agregat tanpa penutup aspalâ€ on Middle Border Gradations Using Clay Stone". The purpose of this study was to determine the value of the mixture composition between clay stone and broken stone, the value of PI content (plastic index) and CBR value â€œLapis Pondasi Agregat tanpa penutup aspalâ€ must meet the requirements of material properties in accordance with the General Revised 3rd Edition of Bina Marga specifications, the gradation consists of material passed the filter Â¾, maximum liquid limit value of 35%, minimum plasticity index value of 4% and maximum 15 %, clumps of clay and fragile granules of at least 0% and a maximum of 5%, coarse aggregate abrasion is a maximum of 40% and has a minimum CBR (California Bearing Ratio) value of 60%. From the results of this study, it can be seen the mixture composition between clay stone and stone, PI value (plastic index) and CBR value from the gradation of the middle boundary of the â€œLapis Pondasi Agregat tanpa penutup aspalâ€. The composition of the mixture of clay stone and aggregate rock broke on the middle boundary gradation, ie 1-2% broken stone by 20%, 1-1 broken stone by 33%, stone ash by 35%, and clay stone by 12%. Based on the results of the examination of the liquid limit and plastic limit, the Plastic Index (PI) value of the clay stone was 35.696% and for the combination of the mixture of broken stone with an additional 12% clay stone was 13.941%. Based on the results of laboratory density and CBR examinations, it was found that the design CBR value of broken stone aggregate was 73%, the clay stone was 1,150% and for the combination of clay stone and aggregate rock was broken by 64%.